Parents refusing treatment of the child: A discussion about child's health right and parental paternalism. (June 2013) - Güvercin, Cemal Hüseyin; Arda, Berna
In recent years, decision-making processes related to medical practices have undergone a change from physician paternalism towards patient autonomy. However, it has been put forward that this situation has changed into or strengthened the parent paternalism for children. Parental paternalism might bring along decisions of refusing the child's treatment, in such a way to occasionally violate the health right of the child. Paternalistic attitude of parents may also cause physicians to direct towards defensive medicine practices and to display a tendency of avoiding legal liability rather than the benefit of the patient. Coming to the decision of the parent on refusing the child's treatment together defensive medicine approach of the physician and an environment, where the legal protection mechanisms for the child are not efficient enough, causes serious violations of health rights. International contracts and national law require the protection of the child's best interest in all cases. In that case, parent's decision on refusing treatment of the child should be restricted within the scope of the child's best interest and healthy life right.